Nutritional, physiological, and perceptual responses during a summer ultraendurance cycling event - Armstrong, L. E.; Casa, D. J.; Emmanuel, H.; Ganio, M. S.; Klau, J. F.; Lee, E. C.; Maresh, C. M.; McDermott, B. P.; Stearns, R. L.; Vingren, J. L.; Wingo, J. E.; Williamson, K. H.; et al. (The Journal of Strength and Conditioning Research, 2012)
Despite the rapid growth of mass participation road cycling, little is known about the dietary, metabolic, and behavioral responses of ultraendurance cyclists. This investigation describes physiological responses, perceptual ratings, energy balance, and macronutrient intake of 42 men (mean ± SD; age, 38 ± 6 years; height, 179.7 ± 7.1 cm; body mass, 85.85 ± 14.79 kg) and 6 women (age, 41 ± 4 years; height, 168.0 ± 2.9 cm; body mass, 67.32 ± 7.21 kg) during a summer 164-km road cycling event. Measurements were recorded 1 day before, and on the Event Day (10.5 hours) at the start (0 km), at 2 aid stations (52 and 97 km), and at the finish line (164 km). The ambient temperature was >39.0° C during the final 2 hours of exercise. The mean finish times for men (9.1 ± 1.2 hours) and women (9.0 ± 0.2 hours) were similar, as were mean gastrointestinal temperature (TGI), 4 hydration biomarkers, and 5 perceptual (e.g., thermal, thirst, pain) ratings. Male cyclists consumed enough fluids on the Event Day (5.91 ± 2.38 L; 49% water) to maintain body mass within 0.76 kg, start to finish, despite a sweat loss of 1.13 ± 0.54 L·h-1 and calculated energy expenditure of 3,115 kcal·10.5·h-1. However, men voluntarily underconsumed food energy (deficit of 2,594 kcal, 10.9 MJ) and specific macronutrients (carbohydrates, 106 ± 48 g; protein, 8 ± 7 g; and sodium, 852 ± 531 mg) between 0530 and 1400 hours. Also, a few men exhibited extreme final values (i.e., urine specific gravity of 1.035-1.038, n = 5; body mass loss >4 kg, n = 2; TGI, 39.4 and 40.2°C). We concluded that these findings provide information regarding energy consumption, macronutrient intake, hydration status, and the physiological stresses that are unique to ultraendurance exercise in a hot environment.